Unleashing Central America's Growth Potential - Ulku, Hulya; Zaourak, Gabriel (World Bank, Washington, DC, 2021)
Central America’s priority is to recover from its deepest economic contraction and restore strong, sustainable economic growth. With increases in working age population projected to decline sharply, strong growth in the long run can only be achieved with higher productivity. More effective participation in global value chains (GVCs), as well as a robust shift towards sophisticated exports of goods and services will be needed, but neither can be ensured without firms investing in productivity-enhancing innovations. With a high likelihood of limited structural change, greater aggregate productivity must come from within each sector of manufacturing, services and agriculture. The synthesis report analyzes the main findings of the Unleashing Central America’s Growth Potential Study, focusing on productivity and export performance of the region over the past three decades and accounting for the impact of the Coronavirus (Covid-19) pandemic on the region. It aims to identify broad strategic directions for the region that would help to increase sophistication of exports, reduce productivity gaps within the region and vis-à-vis other regions, and achieve higher productivity growth. Where relevant, the report suggests areas for further work that could help develop more granular policy recommendations. The rest of this synthesis report is organized as follows: the first section provides an overview of the growth performance of the region over the last thirty years, and provides the current and future challenges facing the region; the second section reviews the performance of productivity growth during 1991-2017; and the third section reviews the growth of exports of goods and services during 1991-2017.